2016
DOI: 10.1590/0100-69912016005013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anxiety, depression and quality of life with the intensity of reflex sweating after thoracoscopic sympathectomy for treatment of primary hyperhidrosis

Abstract: a simpatectomia torácica por videotoracoscopia melhora a qualidade de vida de pacientes com hiperidrose primária, mesmo com o surgimento de sudorese reflexa. A ansiedade está diretamente relacionada com a intensidade da sudorese reflexa, sem comprometer o grau de satisfação do paciente.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…All studies evaluating patients' quality of life as the focus showed similar results regarding patients' satisfaction with the outcome of hyperhidrosis elimination [4][5][6][7][8][9][10][11][12][13][14] (Table 1). In this study, 15 subjects underwent resympathectomy.…”
Section: Resultsmentioning
confidence: 97%
“…All studies evaluating patients' quality of life as the focus showed similar results regarding patients' satisfaction with the outcome of hyperhidrosis elimination [4][5][6][7][8][9][10][11][12][13][14] (Table 1). In this study, 15 subjects underwent resympathectomy.…”
Section: Resultsmentioning
confidence: 97%
“…Baseline assessment reflected clinically elevated scores across most measures, with subsequent scores falling into the nonclinical range for both sweat symptoms and psychosocial functioning. Intervention studies have found improvements in psychosocial functioning with sympathectomy [6‐9] and botox [11‐13].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the preponderance of social anxiety and negative emotional states among individuals with hyperhidrosis, several studies have examined the effects of treatments to reduce sweat production on psychosocial functioning. Sympathectomy has been associated with improved QOL [3‐6], reduced social stress and anxiety [6‐9], reduced psychiatric medication prescriptions [10], and decreased depressive symptoms [6,8]. Botulinum toxin treatment has likewise been shown to improve QOL [11], reduce social anxiety [12], and decrease negative mood states of anxiety and depression [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…11,12,13 However, only a few studies have assessed CS and if its intensity affects the QOL of patients, but the results were inconsistent. Dias et al 14 proposed that CS potentially worsens postoperative QOL. Chang and colleagues' 15 retrospective review reported that overall satisfaction of patients was inversely correlated with the severity of CS.…”
Section: Introductionmentioning
confidence: 99%